How do retail investors react to a market crash? The role of investment literacy. Issue 6 (30th March 2023) - Kim, Hohyun; Kim, Kyoung Tae
ABSTRACT: This study investigates retail investors' behaviour when the US stock market dropped precipitously by 10% in early February 2018. Results show that investors with higher investment literacy were more likely to buy additional stocks and less likely to sell their stocks, which indicates that they expected a quick recovery of the market. We also find that older investors and investors with greater risk aversion were more likely to hold their positions without buying or selling stocks. Similar evidence is found in reactions to a 20% hypothetical market drop. This study sheds light on the meagre literature on retail investors' behaviour during market crash.